2016
DOI: 10.5114/fmpcr.2016.63700
|View full text |Cite
|
Sign up to set email alerts
|

Students’ opinions on working in rural practice in Slovenia

Abstract: Background. All over the world, there is a lack of interest for specialty training in family medicine and for work in rural practice. Objectives. The objective of our study was to survey the opinion of medical students of the Maribor Medical Faculty, Slovenia, about rural medicine. Material and methods. This was a qualitative study. A semi-structured questionnaire with open-ended questions was used. In the period from December 2013 to February 2014, an electronic form was forwarded via e-mail to a stratified s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…clinical associates (a mid-level Phc health practitioner), for example, are allowed to prescribe limited psychotropic medications with some legal restrictions, even though they are not specialist trained in Mhc. clinical associates and medical students have also now started to receive practical training in rural and PHC settings [44], an approach advocated as having positive effects on healthcare students' opinions of later working in these settings [45].…”
Section: Human Resource Productionmentioning
confidence: 99%
“…clinical associates (a mid-level Phc health practitioner), for example, are allowed to prescribe limited psychotropic medications with some legal restrictions, even though they are not specialist trained in Mhc. clinical associates and medical students have also now started to receive practical training in rural and PHC settings [44], an approach advocated as having positive effects on healthcare students' opinions of later working in these settings [45].…”
Section: Human Resource Productionmentioning
confidence: 99%
“…Furthermore, studies have also revealed the negative aspects of a family doctor's specialty, such as managerial orientation, professional isolation and the need to compile excess documentation, low prestige and intellectual level, as well as the extremely wide, unlimited and general scope [15]. Medical students are scared of the government's pressure, as they seem to try to force newly graduated family doctors to work in remote or rural areas [16,17]. Family physicians are also facing some difficulties, such as overwork, stress and dissatisfaction with medical practice, and they are forced to provide medical care to patients during non-working hours in emergencies [18].…”
Section: Introductionmentioning
confidence: 99%